Distribution of onchocercosis in horses caused by Onchocerca cervicalis Rail-liet et Henry, 1910 and O. reticulata Diesing, 1841, in the region of East Caucasus - R. I. Hasanova (Российский паразитологический журнал, 2016)
Distribution of onchocercosis in the conditions of East Caucasus is studied by the method of dermolarvoscopy of 199 horses and helminthological autopsy of a cervical sheaf and sinews of extremities of 118 horses. Onchocercosis is wide dis-tributed in Chechen Republic. The extensity of infection of horses with Onchocerca spp. on areas fluctuates from 23,0 to 41,6 % that, on average, makes 32,66 % at detection in 100 mg of skin of 95,2–181,4 expl. of microfilariae. Extensiveness of the infection caused by Onchocerca cervicalis, O. reticulatа and both types made respectively 25,42 %, 5,93 and 2,54 %. The maximum contamination of horses is noted in foothill zone. Contamination of horses with age considerably raises. Max-imum contamination is established in horses at the age of 6–8 years. It is noted dif-ferences in age dynamics of horses infection with O. cervicalis and O. reticulatа.